If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + -4)(a + -5) = 0 Reorder the terms: (-4 + a)(a + -5) = 0 Reorder the terms: (-4 + a)(-5 + a) = 0 Multiply (-4 + a) * (-5 + a) (-4(-5 + a) + a(-5 + a)) = 0 ((-5 * -4 + a * -4) + a(-5 + a)) = 0 ((20 + -4a) + a(-5 + a)) = 0 (20 + -4a + (-5 * a + a * a)) = 0 (20 + -4a + (-5a + a2)) = 0 Combine like terms: -4a + -5a = -9a (20 + -9a + a2) = 0 Solving 20 + -9a + a2 = 0 Solving for variable 'a'. Factor a trinomial. (4 + -1a)(5 + -1a) = 0Subproblem 1
Set the factor '(4 + -1a)' equal to zero and attempt to solve: Simplifying 4 + -1a = 0 Solving 4 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1a = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1a = 0 + -4 -1a = 0 + -4 Combine like terms: 0 + -4 = -4 -1a = -4 Divide each side by '-1'. a = 4 Simplifying a = 4Subproblem 2
Set the factor '(5 + -1a)' equal to zero and attempt to solve: Simplifying 5 + -1a = 0 Solving 5 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1a = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1a = 0 + -5 -1a = 0 + -5 Combine like terms: 0 + -5 = -5 -1a = -5 Divide each side by '-1'. a = 5 Simplifying a = 5Solution
a = {4, 5}
| (x-7)(x^2-3x+5)= | | -5+(-5)+(-5)+(-5)[(-3)+(-3)+(-3)+(-3)+(-3)]= | | 0.05n+010d=1.30 | | 005n+0.10d=16 | | 0.05+0.10=16 | | 3c/15=8.8 | | 0.05n+0.10d=1.30 | | -5+(-5)+(-5)+(-5)+[(-3)+(-3)+(-3)+(-3)+(-3)]= | | p=-5x^2+13x-4 | | 20n=2n+30 | | -4x+5=x^2 | | 2.7timesb=54 | | (6x+9)-(15x-3)=-6 | | 3x^4-4x^3-30x^2-36x+10=0 | | 4.50x=4.0x+2 | | 6x+25-2=6+23x-2 | | -16=5x-3+b | | 4.50x=3.75x+4 | | (12x-4)+(10-2x)=36 | | 49y=6(-8y-4) | | (20/(p-4))-((5p)/(p-4)) | | 2x-5=2x+15 | | F(x)=3sin(x-4)+5 | | 4x+2=3.75+4 | | (X+9)(X^2+5X+9)= | | 11=8y-5 | | x^4+10*x^3+14*x^2-8=0 | | 4x+(2x-12)=42 | | 2-(3x+1)+6=15 | | 9x*9=15 | | sin(5x)-sin(3x)=cos(4x) | | -64x^2+16=0 |